The simple production of nonsymmetric quaterpyridines through Kröhnke pyridine synthesis - Sasaki, Isabelle; Daran, Jean-Claude; Commenges, Gérard (Beilstein Journal of Organic Chemistry, 2015)
Quaterpyridines have been demonstrated to be useful building blocks in metallo-supramolecular chemistry; however, their synthesis requires the preparation of sensitive building blocks. We present here three examples of nonsymmetric quaterpyridines that were easily obtained in yields of 70–85% by condensation of commercially available enones with 6-acetyl-2,2’:6’,2’’-terpyridine through a Kröhnke pyridine synthesis. Easy access to 6-acetyl-2,2’:6’,2’’-terpyridine starting from 2,6-diacetylpyridine and 2-acetylpyridine is described. The X-ray analysis of a chiral quaterpyridine and its Pt(II) complex is presented.
Keywords: heterocycles; Kröhnke pyridine synthesis; Mannich bases; platinum; X-ray diffraction